KEBERLANJUTAN : TANTANGAN PROGRAM SOCIAL MARKETING UNTUK PERUBAHAN SOSIAL - Setyabudi, Djoko (FORUM)
Abstract :Â This article discusses about the major problem faced by Social marketing program that is sustainability. Four important aspects that ensure sustainability is economic, social, environmental and cultural. The social marketing program built based on the alignment of the its have a hope of being able to survive in the midst of the community, however the factor of political and Government support remains needed. The upstream approach to lobbying the authorities will increasingly ensure social marketing programs run well.Keywords : social marketing, social change, sustainabilitypermalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3201